Pak2 is essential for the function of Foxp3+ regulatory T cells through maintaining a suppressive Treg phenotype. Issue 1 (December 2017) - O'Hagan, Kyle; Miller, Stephen; Phee, Hyewon
Abstract Foxp3, a key transcription factor that drives lineage differentiation of regulatory T cells (Tregs), was thought to imprint a unique and irreversible genetic signature within Tregs. Recent evidence, however, suggests that loss or attenuation of Foxp3 expression can cause Tregs to de-differentiate into effector T cells capable of producing proinflammatory cytokines. Herein, we report that the signaling kinase, p21-activated kinase 2 (Pak2), is essential for maintaining Treg stability and suppressive function. Loss of Pak2, specifically in Tregs, resulted in reduced expression of multiple Treg functional molecules, including Foxp3, CD25, Nrp-1 and CTLA-4, coupled with a loss of Treg suppressive functionin vitro andin vivo . Interestingly, Pak2-deficient Tregs gained expression of Th2-associated cytokines and the transcription factor, Gata3, becoming Th2-like cells, explaining their inability to regulate immune responses. Collectively, these findings suggest Pak2 as an important signaling molecule for guarding against aberrant immune responses through regulating the stability of Foxp3+ Tregs and maintaining a suppressive Treg phenotype.